Self efficacy dan organizational citizenship behavior - Yanto Prasetyo; Diah Sofiah; Hikmah Husniyah Farhanindya (INNER: Journal of Psychological Research, 2022)
This study aims to explain the relationship between Self Efficacy and Organizational Citizenship Behavior (OCB) in Polri members. This study uses a quantitative method with a spread of scale in data collection. The research subjects were members of the East Java Police Ditintelkam. The number of subjects is 100 people. The scale used is a measuring tool from Schwarzer, R., & Jerusalem, M, namely the Self Efficacy scale. Organizational Citizenship Behavior Scale using measuring tools from Organ. Research data were analyzed using Spearman Brown correlation test. The hypothesis proposed in this study was accepted with the test results showing a Pearson correlation coefficient of 0.395 with a level of sig = 0.000 <0.05. These results explain that there is a significant relationship between Work Self Efficacy and Organizational Citizenship Behavior in Ditintelkam members. High and low self-efficacy can affect the low organizational citizenship behavior. The higher the Work Engagement, the higher the Organizational Citizenship Behavior. Keywords: Organizational Citizenship Behavior; Self Efficacy